Lightest flavor-singlet qqq baryons as witnesses to color - Estévez, Jonathan; Llanes-Estrada, Felipe J.; Martínez-Fernández, Víctor; Pastor-Gutiérrez, Álvaro (Physical review, 2020)
We present a new computation in a field-theoretical model of Coulomb-gauge QCD of the first radial and angular excitations of a qqq system in an SU(3) flavor-singlet state, ΛS. The traditional motivation for the study is that the absence of flavor singlets in the lowest-lying spectrum is a direct consequence of the color degree of freedom. [The calculation is tested with decuplet baryons Δ(1232) and Ω(1672).] We also analyze decay branching fractions of the flavor-singlet baryon for various masses with the simplest effective Lagrangians.
Gesehen am 08.02.2022